1980
DOI: 10.1530/acta.0.0930175
|View full text |Cite
|
Sign up to set email alerts
|

The effects of iopodate on the serum iodothyronine pattern in normal subjects

Abstract: The ingestion by normal subjects of 3 g of sodium iopodate, which is widely used in routine oral cholecystography, resulted in significant decreases of serum total and free T3 to a nadir on day 4 which averaged 43% and 40%, respectively, below initial mean values. Total and free rT3 increased markedly to a peak on day 3, 244% and 189%, respectively, above initial mean values. Total and free Ti and free T4 index rose to a maximum on day 4, but these changes were not statistically significant. A marked TSH incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 3 publications
(4 reference statements)
2
14
0
Order By: Relevance
“…The most widely studied agents in humans are sodium ipodate and iopanoic acid. With the administration of either agent, serum triiodothyronine (T 3 ) and free T 3 levels fall while rT 3 levels increase (1,2,(14)(15)(16) (Fig. 1).…”
Section: Effects On Thyroid Hormone Physiologymentioning
confidence: 99%
See 3 more Smart Citations
“…The most widely studied agents in humans are sodium ipodate and iopanoic acid. With the administration of either agent, serum triiodothyronine (T 3 ) and free T 3 levels fall while rT 3 levels increase (1,2,(14)(15)(16) (Fig. 1).…”
Section: Effects On Thyroid Hormone Physiologymentioning
confidence: 99%
“…Thus, there is reduction in peripheral as well as intrapituitary conversion of thyroxine (T 4 ) to T 3 and diminished degradation of rT 3 . Basal and TRH-stimulated thyrotropin (TSH) values have been shown to increase or remain unchanged (2,(14)(15)(16)(22)(23)(24)(25)(26). In hyperthyroid subjects with Graves' disease, where there is increased expression of 59-MDI, T 4 levels decrease or remain unchanged (10,(27)(28)(29)(30)(31).…”
Section: Effects On Thyroid Hormone Physiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, as 500 mg of SI contains 308 mg iodine, large amounts of iodine are released during its metabolism, resulting in the inhibition of the organifica tion of iodine (Wolff-Chaikoff effect) [5] and of thyroid hormone release [6], Furthermore, SI seems to inhibit the hormonal secretion of the thyroid also by a direct effect which is independent of the inhibition induced by iodine [3,7,8]. It has been shown that during treatment with SI plasma T4 values decrease by 20-31 % in thyro toxic Graves' patients [1,[9][10][11][12][13], but remain unchanged or even rise in healthy adults [1,14,15]; on the other hand, plasma T3 values decrease by 67-76% in thyro toxic Graves' patients and by 25-55% in healthy adults [1,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%